IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN DALAM LAYANAN PROFESI KONSELING - Mardiyani, Ani (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
With the advent of PP No. 19/2005 on National Education Standards (SNP), Permendiknas Permendiknas No. 24/2006 No. 22/2006 on the Implementation of Content Standards for Elementary and Secondary Education Unit, and No. 23/2006 on Graduates Competency Standards for Basic Education Unit and Medium, then we know the curriculum (Education Unit Level Curriculum). On the structure of the curriculum SD / MI, SMP / MTs. SMA / MA, and appropriate vocational curriculum, there were a series of Subjects at point A, point B on the Local Content, andDevelopment at point C. Subjects are taught by subject teachers, class teachers or teachers’ practice; local charge as extracurricular activities; While the development itself is not a subject that must be nurtured by a teacher but is facilitated and or guided by a counselor, teacher or educational staff that can be done in form of extra-curricular activities. Self-development activities conducted through activities of counseling services related to personal problems and social life, learning, and career development of students. As a mentor teacher or counselor at school need to understand the implementation of the curriculum in professional counseling services, so as to demonstrate its performance as a professional counselor. Which in turn will improve the quality of education in the global competition.